Salt : a story of friendship in a time of war - Frost, Helen, 1949- (Frances Foster Books, 2013)
Twelve-year-olds Anikwa, of the Miami village of Kekionga, and James, of the trading post outside Fort Wayne, find their friendship threatened by the rising fear and tension brought by the War of 1812.